Experimental Evaluation of Food-Grade Semi-Refined Carrageenan Toxicity - Pogozhykh, Denys; Posokhov, Ye. O.; Myasoedov, Valeriy; Gubina-Vakulyck, Galina; Chumachenko, Tetyana; Knigavko, Oleksandr; Polikarpova, Hanna; Kalashnyk-Vakulenko, Yuliia; Sharashydze, Ketino; Nakonechna, Oksana; Prokopyuk, Volodymyr; Onishchenko, Anatolii; et al. (My University, 2021)
The safety of food additives E407 and E407a has raised concerns in the scientific community. Thus, this study aims to assess the local and systemic toxic effects of the common food additive E407a in rats orally exposed to it for two weeks. Complex evaluations of the effects of semi-refined carrageenan (E407a) on rats upon oral exposure were performed. Local effects of E407a on the intestine were analyzed using routine histological stains and CD68 immunostaining. Furthermore, circulating levels of inflammatory markers were assessed. A fluorescent probe O1O (2-(20-OH-phenyl)-5-phenyl-1,3-oxazole) was used for evaluating the state of leukocyte cell membranes. Cell death modes of leukocytes were analyzed by flow cytometry using Annexin V and 7-aminoactinomycin D staining. Oral administration of the common food additive E407a was found to be associated with altered small and large intestinal morphology, infiltration of the lamina propria in the small intestine with macrophages (CD68+ cells), high systemic levels of inflammation markers, and changes in the lipid order of the phospholipid bilayer in the cell membranes of leukocytes, alongside the activation of their apoptosis. Our findings suggest that oral exposure to E407a through rats results in the development of intestinal inflammation.
Keywords: carrageenan; E407a; processed Eucheuma seaweed; toxicity; fluorescent probe; leukocytes; inflammation; intestine; animal model